Bicultural identity in Saud Alsanousi’s The Bamboo Stalk - Areej Almutairi; Raihanah M.M.; Ruzy Suliza Hashim (Penerbit Universiti Kebangsaan Malaysia, 2019)
Although the world now has largely become a global village, some bicultural individuals still find it challenging to be accepted into certain societies. Building on this argument, this article analyzes the struggles faced by the bicultural character in The Bamboo Stalk (2015), a novel written by the Kuwaiti writer, Saud Alsanousi. Jose is the son of a Filipino maid and a wealthy Kuwaiti man. Upon birth, he was disowned by his paternal family and was forced to leave for Manila with his mother, to be raised in poverty. In this article, the theory of graft by Colin Richards and selected concepts on biculturalism are appropriated to explore the manifestations of the grafted individual’s identity construction, demonstrating how grafting carries a negative impact in the formation of the individual’s social, religious and national identities. The narrative depicts the protagonist’s dilemma and identity crisis, revealing the circumstances that has led to the formation of his split identity. While the grafted individual finds it challenging to ascertain his identity that lies between two vastly different and incompatible cultures, the majority societies in the two cultures do not accept him for who he really his. This paper therefore highlights the experience of the bicultural in establishing a clear grafted identity as presented in Alsanousi’s work.